2018
DOI: 10.1021/acs.macromol.8b00193
|View full text |Cite
|
Sign up to set email alerts
|

Thermoresponsive Hydrogels Based on Telechelic Polyelectrolytes: From Dynamic to “Frozen” Networks

Abstract: A novel thermoresponsive gelator of (B-co-C)-b-A-b-(B-co-C) topology, comprising a poly­(2-(dimethyl­amino)­ethyl methacrylate) (PDMAEMA) weak polyelectrolyte as central block, end-capped by thermosensitive poly­(triethylene glycol methyl ether methacrylate/n-butyl methacrylate) [P­(TEGMA-co-nBuMA)] random copolymers, was designed and explored in aqueous media. The main target of this design was to control the dynamics of the stickers by temperature as to create an injectable hydrogel that behaves as a weak ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
57
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 61 publications
10
57
1
Order By: Relevance
“…The change in solvent quality (or temperature) influences the exchange dynamic of end blocks, leading to the exponential increase of network relaxation time of gel upon cooling (Figure 2b and Figure 3). This argument is also supported by the results reported by Tsitsilianis et al 22 . They tuned the lifetime of end block associations and found that the relaxation time of gel network strongly depends on the lifetime of end block associations.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The change in solvent quality (or temperature) influences the exchange dynamic of end blocks, leading to the exponential increase of network relaxation time of gel upon cooling (Figure 2b and Figure 3). This argument is also supported by the results reported by Tsitsilianis et al 22 . They tuned the lifetime of end block associations and found that the relaxation time of gel network strongly depends on the lifetime of end block associations.…”
Section: Resultssupporting
confidence: 87%
“…10 -8 10 -6 10 -4 10 -2 10 0 10 2 10 -2 From the temperature dependent aT, the longest relaxation time of the system at any given temperature can be obtained by the relation 1,14,22 :…”
Section: Resultsmentioning
confidence: 99%
“…It is known that the relative hydrophobicity of PNIPAM is low above its LCST, as PNIPAM never becomes totally hydrophobic, even well above its cloud point [ 23 ]. Thus, by using random copolymers enriched with hydrophobic moieties, we can regulate not only the LCST but also the hydrophobic association in terms of exchange dynamics of the stickers of the network that control the rheological properties [ 22 , 24 , 25 , 26 , 27 ]. The objective of the present work is to address the above issue by studying the effect of the hydrophobic content of the associative grafting P(NIPAM x - co -NtBAM y ) chains of alginate-based graft copolymers, attempting to tailor the T gel , and in turns all the properties of the hydrogel formulations, including injectability at relatively low gelator concentration.…”
Section: Introductionmentioning
confidence: 99%
“…The investigation of physically cross-linked networks by simulations are scarce. Exceptions worth mentioning are the investigations of associating polymers, so-called telechelic polymer chains [29][30][31][32][33][34] , as well as the investigation of ionomers [35][36][37][38][39] and neutral block starshaped copolymers 34 ; these, however, do not fall into the class of strongly swelling, ionically reversible cross-linked stars. Many theories also deal with the swelling of chemical gels, but much less with the swelling behaviour of physical ones.…”
Section: September 6 2020 1 Introductionmentioning
confidence: 99%